2001
DOI: 10.1046/j.1198-743x.2001.00275.x
|View full text |Cite
|
Sign up to set email alerts
|

Brucella detection in blood: comparison of the BacT/Alert standard aerobic bottle, BacT/Alert FAN aerobic bottle and BacT/Alert enhanced FAN aerobic bottle in simulated blood culture

Abstract: The objective of this study was to compare the performances of the standard aerobic bottle (StAe), FAN aerobic (FANAe) and enhanced FAN aerobic (E-FANAe) (the charcoal component of the FANAe was revised recently to improve the feasibility of Gram smear interpretation) blood culture bottles for BacT/Alert system for the detection of Brucella melitensis in simulated blood culture. Triplicate strains of eight clinical isolates of B. melitensis were studied. Each bottle was inoculated with 5 mL of freshly collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
0
7
0
4
Order By: Relevance
“…One study reported a mean detection time of 51.2 ± 8.2 hours using BacT/ALERT standard aerobic bottles [7]. Another investigation showed the mean detection time of Brucella spp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study reported a mean detection time of 51.2 ± 8.2 hours using BacT/ALERT standard aerobic bottles [7]. Another investigation showed the mean detection time of Brucella spp.…”
Section: Resultsmentioning
confidence: 99%
“…The diagnosis of brucellosis based on blood culture may be challenging because a relatively low sensitivity is associated with the disease progress. There is different performance among different blood culture systems [7,16]. Both BacT/ALERT and BACTEC FX blood culture systems are widely used to recover Brucella spp.…”
Section: Discussionmentioning
confidence: 99%
“…One of the important reason for this faulty is poorly organized health centers that not operate harmoniously for true case definitions throughout the country. Sümerkan et al (22), have reported that approximately 50-60 B. melitensis were isolated from 8000 blood samples per year in Kayseri and that Brucellosis caused by B. melitensis was endemic in this region. Also in this study, a total of 50 Brucella spp.…”
Section: Discussionmentioning
confidence: 99%
“…El diagnóstico microbiológico obedece a la doble estrategia apuntada de acuerdo con lo expresado en la tabla VIII. Como método de diagnóstico directo mantiene su vigencia el asisla- miento con un nivel de bioseguridad exigible a un agente de clase 3, a partir fundamentalmente de hemocultivos (107,108), cultivo de médula ósea (109) o de muestras representativas de la amplia gama de focalidades clínicas que es capaz de originar. En la actualidad el rendimiento de los métodos de cultivo clásicos como el bifásico de Castañeda se ha visto mejorado por los sistemas comerciales automatizados (107).…”
Section: Brucelosisunclassified